2016
DOI: 10.4103/0019-5154.190115
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intense pulsed light therapy in the treatment of facial acne vulgaris: Comparison of two different fluences

Abstract: Background:Acne vulgaris is the most common disease of the skin affecting adolescents and young adults causing psychological distress. The combination of antibiotic resistance, adverse effects of topical and systemic anti acne medications and desire for high tech approaches have all led to new enthusiasm for light based acne treatment. Intense pulse light (IPL) therapy has three modes of action in acne vulgaris i.e., photochemical, photo thermal and photo immunological.Aims:(1) to study efficacy of IPL therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…They appear to target the pathogenetic factors of acne by reducing inflammatory acne lesions, decreasing sebaceous gland activity and inhibiting C. acnes . More recently, various lasers such as the 585 and 595 nm pulsed dye lasers, 532 KTP laser, 1450 nm diode laser, 1540 nm erbium glass laser, intense pulsed light and radiofrequency devices have been used for the treatment of inflammatory acne vulgaris, but are not very effective for comedonal lesions 67–69. They also have the advantage of improving post acne scars.…”
Section: Methodsmentioning
confidence: 99%
“…They appear to target the pathogenetic factors of acne by reducing inflammatory acne lesions, decreasing sebaceous gland activity and inhibiting C. acnes . More recently, various lasers such as the 585 and 595 nm pulsed dye lasers, 532 KTP laser, 1450 nm diode laser, 1540 nm erbium glass laser, intense pulsed light and radiofrequency devices have been used for the treatment of inflammatory acne vulgaris, but are not very effective for comedonal lesions 67–69. They also have the advantage of improving post acne scars.…”
Section: Methodsmentioning
confidence: 99%
“…Crusting, bulla formation and hyperpigmentation were observed in four, one and two patients respectively but these resolved within 1 to 2 weeks. Patidar MV et al 11 reported itching in forty patients, erythema in two patients, burning sensation in three patients and two patients developed milia.…”
Section: Discussionmentioning
confidence: 99%
“…10 IPL in acne vulgaris works by photochemical, photothermal and photo-immunological process. 11,12 The photochemical reaction seen in acne vulgaris lesions is through its action on porphyrins produced by the P. acnes bacteria themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Other medications frequently used for treating acne included retinoids, traditional Chinese medicine (TCM) and benzoyl peroxide (BPO). The new treatments included intense pulsed light (IPL), blue and red light, photodynamic therapy (PDT), radiofrequency (RF) and alpha hydroxy acid (AHA) 19–23…”
Section: Introductionmentioning
confidence: 99%